2002
DOI: 10.1016/s0375-9601(02)00473-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial solitons in a medium composed of self-focusing and self-defocusing layers

Abstract: We introduce a model combining Kerr nonlinearity with a periodically changing sign ("nonlinearity management") and a Bragg grating (BG). The main result, obtained by means of systematic simulations, is presented in the form of a soliton's stability diagram on the parameter plane of the model; the diagram turns out to be a universal one, as it practically does not depend on the soliton's power. Moreover, simulations of the nonlinear Schrödinger (NLS) model subjected to the same "nonlinearity management" demonst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…However, this same model based on Eqs. (1) and (2) can be interpreted to another physical system in the spatial domain [31,32], if the variable τ in the Eqs. (1, 2) is replaced by the transverse coordinate x.…”
Section: Theorymentioning
confidence: 99%
“…However, this same model based on Eqs. (1) and (2) can be interpreted to another physical system in the spatial domain [31,32], if the variable τ in the Eqs. (1, 2) is replaced by the transverse coordinate x.…”
Section: Theorymentioning
confidence: 99%
“…Many experiments showed that the LiNbO 3 : Fe crystals are self-defocusing dielectric materials, for the photo-induced refractive index change, ∆n, is negative, ∆n <0, which tends to form dark spatial solitons. In recent years, researchers had succeeded in observing the dark spatial solitons in LiNbO 3 : Fe crystals [14,15].…”
Section: Vmentioning
confidence: 99%
“…Another model, which combines the NLM with the effective dispersion (actually, diffraction, as the model was realized in the spatial domain) induced by the Bragg grating, was investigated too [21]. It is composed of alternating BGs with opposite signs of the Kerr nonlinearity, and also gives rise to a family of robust solitons.…”
Section: Wimentioning
confidence: 99%
“…(4.8), (4.9), (4.11), and (4.13) were also studied in work [21]. In particular, two identical solitons with an initial phase difference Acj) attract each other if A^ = 0 (see Fig.…”
Section: Interactions Between Sohtons and Generation Of Moving Solitonsmentioning
confidence: 99%